Reactions of 1‐Arylbenziodoxolones with Azide Anion: Experimental and Computational Study of Substituent Effects. Issue 5 (2nd February 2018) - Yusubov, Mekhman S.; Soldatova, Natalia S.; Postnikov, Pavel S.; Valiev, Rashid R.; Svitich, Dmitry Y.; Yusubova, Roza Y.; Yoshimura, Akira; Wirth, Thomas; Zhdankin, Viktor V.
Abstract : New substituted 1‐arylbenziodoxolones were prepared and their reactivity with azide anion as a nucleophile was investigated. It was found that independent of the presence of substituents, all reactions of 1‐arylbenziodoxolones proceed as nucleophilic substitution of the iodonium leaving group in the electron‐deficient benziodoxolone benzene ring. The presence of bulky substituents in the ortho position of the aryl ring slows the reaction down, while the presence of a moderately electron‐withdrawing bromine substituent in para position to the iodine atom in the benziodoxolone ring moderately increases the rate of substitution. The presence of a strongly electron‐withdrawing nitro group in the para position to the iodine atom in the benziodoxolone ring dramatically increases the rate of substitution. These observations are in agreement with the electronic requirements for internal nucleophilic substitution in the benziodoxole ring. A quantum‐chemical computational study of the possible reaction paths is in agreement with the observed effects of substituents on the reactivity of arylbenziodoxolones in this reaction. Abstract : Several new substituted 1‐arylbenziodoxolones were prepared and their reactivity with azide anion as a nucleophile was investigated by experimental and computational studies.